In vitro study for the evaluation of transluminal aspiration as a novel treatment option for thrombosis in the HeartWare HVAD. Issue 11 (November 2018) - Gärtner, Theresa; Beropoulis, Efthymios; Wendl, Regina; Hanke, Jasmin S; Dogan, Günes; Chatterjee, Anamika; Haverich, Axel; Torsello, Giovanni; Schmitto, Jan D; Bisdas, Theodosios; Feldmann, Christina
Introduction: Pump thrombosis of left ventricular assist devices remains a devastating complication with high morbidity and mortality. Despite the improvements made, the matter affects many patients and the treatment options are limited to thrombolysis and surgical replacement. An alternative approach using the aspiration Indigo catheter was tested. Methods: An Indigo thrombectomy catheter was used within an in vitro model to assess the direct aspiration of prefabricated clots from three different positions within the HeartWare HVAD (inlet, outlet, and housing). The experiments were conducted with a straight and an angled catheter. The aspiration pressure was constant. The flow, power consumption, and pressure head of the left ventricular assist devices were measured at pre-defined measuring points. Results: The device was more effective (success rate 71%) at inlet and outlet of the left ventricular assist device. In addition, the duration of aspiration and the aspiration volume were shorter in comparison to the aspiration in the housing (inlet M  = 19.75 s, outlet M  = 60.50 s, and housing M  = 38.75 s). Moreover, the aspiration volume was associated with the aspiration duration and the weight of thrombi but not with their volume. Noteworthy, the angled catheter showed an improved performance compared to the straight one (67%–33%). The recorded parameters showed no major changes during the use of the catheter. After application of the Indigo catheter, flow and pressure head of the pump could be restored. Conclusions: The aspiration system showed promising results under specific conditions for the treatment of pump thrombosis in an in vitro model. However, further examination, including in vivo experiments, will justify its effectiveness.